The Emergence of Knowledge-Based Technologies in Promoting Knowledge Sharing Behavior (Review of Knowledge Economy, 2015)
This article addresses the emergence of knowledge-based technologies and its focus is on factors that stimulate the successful of knowledge sharing behavior. People nowadays are utilizing knowledge-based and web-based technology, such as Internet, Intranet, social media and other online technology for interaction and collaboration. These are the platforms through which knowledge can be extracted, shared and distributed around the globe and people are starting to communicate and socialize using the latest media and technology. Literature on knowledge sharing and virtual mode suggest the pre-existence of shared knowledge or a shared belief system as a condition for the knowledge-based technologies to emerge. The objective of this study is to analyze the role of these knowledge-based technologies to promote the knowledge sharing behavior. This research uses quantitative methodology for the collection and analysis of data by conducting surveys from the researchers in these organizations. Self-administered questionnaire were distributed to 510 researchers from selected Malaysian Government-Linked Companies (GLCs). The theoretical model developed in this paper is empirically tested on a sample of researchers of five organizations, and significant relationships among these constructs were found. Conclusions and directions for future research are also formulated.